Occurrence of Hypoglycemia, Hypokalemia and Hyperkalemia in Diabetic Hypertensive Patients Using Insulin and Diuretics - A, Sarasmita M; I., Setyawan E.; A., Hendra Jaya (Journal of Health Sciences and Medicine, 2018)
Diabetes Mellitus (DM) is a metabolic disease with characteristics of hyperglycemia that occurs due to insulin secretion abnormalities, insulin work or both. DM can cause macrovascular complications such as hypertension. Administration of therapy may lead to hypoglycemic and hypokalemia that may increase the risk of impaired brain and heart. Objective: The purpose of this study to analyze the incidence of hypoglycemia and hypokalemia side effects in patients with diabetic hypertension using antidiabetes and antihypertensives. Method: The study was conducted retrospectively with retrospective patient medical records from January to December 2016. Blood and potassium blood glucose levels were measured as long as the patient was treated. Random and potassium blood glucose levels prior to therapy were compared with after therapy using paired t-test. Result : From the results of the study found 27 patients suffering from diabetic hypertension and get therapy. The value of changes in the patient's random blood glucose level averaged 280.89 mg/dl to 189.15 mg/dl, which met the target of antidiabetic drug therapy, and no patients had hypoglycemia. From 27 patients, as many as 7 people did not get antihypertensive therapy. Three patients had hyperkalemia (serum potassium level > 5 mEq/L). The value of changes in blood potassium levels of patients averaged 4.74 mEq/L to 4.46 mEq/L, where no patients had hypokalemia. Conclusion : the occurrence of hypoglycemia and hyperkalemia were suspected due to side effect of insulin and antihypertensive drugs.